Sustentabilidade social em um arranjo produtivo local do agronegócio na percepção de seus stakeholders: Um estudo no APL do leite de Santana do Livramento/RS - Mazza, Vera Maria de Souza (2016)
Sustainability has been a theme explored in multifactor analysis interpretations. Among the various dimensions and aspects that are part of this concept complexity, there is the need for better understanding the social related implications. This research seeks to analyze the social sustainability from the perspective of Agribusiness Local Productive Arrangement’ stakeholders, social settings that are structured favoring collective results. The theoretical framework focuses on literature concerning Local Production Arrangements, Stakeholders’ Theory and Social Sustainability. The qualitative approach exploratory research was carried out in the Milk Productive Arrangement of Santana do Livramento, RS in four steps: The first step involved the LPA characterization through secondary data such as records, regulations, documents, minutes of meetings, websites and Graduation Research Projects. The second stage aimed to identify LPA’ stakeholders through the snowball technique. In the third stage semi-structured interviews were conducted, associated with free observation in order to differentiate and categorize the LPA’ stakeholders and analyze social sustainability in the arrangement through content analysis with subsequent categorization of sustainability for analysis. In the fourth stage the results and conclusions were presented. The categories set out in the research analysis comprehend Capital as: natural, economic, physical, human and social. The LPA is characterized by the emergence of its organization because it was not created on based on LPA’s Public Policy but it surged from its stakeholders’ perceived necessity, which led to its entry into LPA’s Public Policies. Were identified 26 stakeholders which were classified highlighting in governance the role of research, education and extension institutions, municipal and federal agencies, Santana do Livramento Milk Producers Cooperative, Technical Service Providers Cooperative. Milk producers are stakeholders with great interest, but its power is considered latent concerning the LPA because many of them are unaware of the LPA and only participate in the annual seminar held by him “Directions of Dairy Basin”. Related to natural capital the concern of interviewed stakeholders lies with the risks that the soybean crop may lead to the use of chemicals affecting human and animal health, and poses a risk to the pampa biome. Regarding the economic capital the production and transport costs and the low value of milk are adamant. The main claim on physical capital is the infrastructure; particularly the precarious state of roads jeopardizes the production and milk transport, reflecting the final price. As well as the les than enough supervision to fresh milk, sold at higher prices. Regarding human capital, according to the stakeholders, it showed improvement as trained agents resulted in milk quality improvement. The social capital highlighted innovation, communication and conflict as relevant points in the study.